Terahertz chemical imaging of a multicomponent tablet in pharmaceutical applications - Katsuhiro Ajito (2018)
Molecular networks based on hydrogen bonds have resonant frequencies in the terahertz (THz) region. THz spectroscopy is a powerful tool for identifying molecular networks created by intermolecular or intra-molecular hydrogen bonds in pharmaceutical and biomedical samples such as drugs, proteins, and cancer cells. A THz chemical imaging (TCI) system was developed by combining a THz time-domain spectrometer with a translational stage to obtain two-dimensional distributions of molecular networks in tablet samples. Since THz spectral peaks of pharmaceuticals are broad at room temperature, multicomponent chemical analysis is limited using the TCI system. In this paper, we describe multicomponent chemical analysis of pharmaceuticals using a sample chamber cooled by a cryostat. TCI measurement at low temperature sharpens spectral peaks and/or shifts peak frequencies, enabling us to determine the distribution of several kinds of pharmaceutical chemicals within a tablet. © 2012 The Electrochemical Society.